PENDAMPINGAN DAN KLINIKAL MENULIS PENTIGRAF BERBAHASA INGGRIS SISWA SMA AL UMANAA BOARDING SCHOOL SUKABUMI - Supriatnoko; Anwar Mustofa (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2026)
The short story writing activity at Al Umanaa Boarding School has become both an in-class and extracurricular assignment, aimed at developing the students' skills. However, this task cannot be completed quickly due to the busy schedule of school and pesantren activities. Therefore, the service team offered the pentigraf (three-paragraph short story) as an alternative short story writing activity. This activity was effectively conducted for 7 days, from August 2 to August 8, 2022, with participants from grades X, XI, and XII of Al Umanaa Boarding School. This community service activity uses service-learning Approach. The methods used included face-to-face meetings, lectures, Q&A sessions, and practical pentigraf writing along with mentoring and clinical assistance during the writing process. The pentigraf writing activity went very smoothly. Generally, each student was able to write three pentigraf works: two in Indonesian and one in English with different themes as the final target of the activity. Evaluation of their works revealed weaknesses in organizing ideas and writing them in English.